New species of Rineloricaria (Siluriformes: Loricariidae) from the Paranaíba River basin, Brazil - Da Costa-Silva, Guilherme José; Oliveira, Claudio; Da Costa E Silva, Gabriel De Souza (Zootaxa, 2021)
Rineloricaria is a genus of armored catfish encompassing 67 valid species that are widely distributed throughout the Neotropical region. A new species of Rineloricaria is described from the Paranaíba River, Upper Paraná River basin, southeastern Brazil. Rineloricaria rodriquezae sp. n. is distinguished from its congeners by the combination of the following characters: caudal-fin color pattern with basal dark spot and subterminal dark bar on branched rays interspersed with a hyaline area; five series of lateral plates with two keeled in the mid-dorsal series around the insertion of the first ray of dorsal fin; and unbranched caudal-fin ray extended as long filaments.